(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the changes in the industrial sector of the Bukhara yarn-gas plant during the years of independence. A number of positive changes in the republic’s light industry were also felt in the textile industry of Bukhara. There was a modernization process in the textile factory. Cooperation agreements in the fields of textile development were signed with a number of foreign countries. To the textile industry of Bukhara during the years of independence its history is discussed.